Measurement System for the Analysis of Social Innovation in Projects - Martez, Nuvia; Dieste, Eugenia (2019 7th International Engineering, Sciences and Technology Conference (IESTEC), 2019)
Recent studies regarding Social Innovation (SI) represent a small percentage of the academic research, and as a consequence the methodologies, focuses, and practices about this topic have not been consolidated. The social innovations generate intangible benefits, mainly qualitative, which makes it difficult to evaluate, even though few authors have indicated the distinguishable characteristics of SI there is not consensus about how to measure it. This document presents the results of a research project with the main objective of identifying the criteria distinguishing SI, and to propose a tool to facilitate its measurement, tracing, and potential assessment. A systematic criteria revision was performed along with a comparative study of eight SI projects from Latin America, prioritizing such criteria. With this information a proposal was developed, including the criteria, associated questions and ponderations. In order to validate the utility of this tool, the evaluation of the project "Implementation of a Solar-Eolic hybrid system in a school in remoted and insolated areas" was performed. The evaluation process allowed to inquire and discover the weaknesses and to explore the limiting causes for every criterion, giving place for recommendations directed to the developers and beneficiaries of the project. Throughout this tool it can be determined whether a project can be considered a successful SI or not; in case of not being successful, the method exerts a simple view of the characteristics that need improvement.
Keywords: Amérique latine; Mesure d'impact; Réservé UdeM